Modification of Spectral Properties of Polystyrene / Diethyl phthalate in Different Solutions - Tawfiq, Esam A.; Kamil, Ghada M. (Iraqi Journal of Science, 2019)
The influence of Diethyl phthalate (DEP) on the optical characteristics of polystyrene solutions in the range between 200 to 400 nm at solvents of different polarities; chloroform, cyclohexane, dichloromethane, and tetrahydrofuran have been recorded. The experimental results showed that the behavior of the photophysical processes of polymer solutions depends on the nature of its environment. The intensity of the absorption and fluorescence spectra depends on the interactions between solvent-solute molecules. The experimental results indicate that the maximum most absorbance bands occur around 262 nm, which depends on the concentration of the quencher. The results did not determine any change in the positions of the most absorption bands. Fluorescence spectra of the polystyrene were measured in chloroform, cyclohexane, dichloromethane, and tetrahydrofuran diluted solutions at room temperature. Fluorescence emission spectra were characterized by one broad main band centered at 295 nm in chloroform and 305 nm in tetrahydrofuran and the emission intensity is dramatically reduced due to strong fluorescence quenching. In cyclohexane and dichloromethane fluorescence spectra of PS/DEP have two bands monomer and excimer emissions at 295 and 328 nm respectively. The presence of DEP quenches the fluorescence and excimer. The excimer emission is more intense. The results showed that the use of different solvents caused a change in the behavior of the fluorescence emission.